2004
DOI: 10.1161/01.str.0000121647.01941.ba
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Ischemic Penumbra with 18 F-Fluoromisonidazole in a Rat Model of Ischemic Stroke

Abstract: Background and Purpose— The ischemic penumbra is a major focus of stroke research. 18 F-fluoromisonidazole ( 18 F-FMISO), a positron emission tomography (PET) marker of hypoxic cells, has shown promise as a technique to image the penumbra in humans. Our aim was to delineate the pattern of 18 F-FMISO binding in a rat middle cerebral artery transient thread-occlusion model, and correlate this with tissue outcome at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…Dynamic progression of lesion volume over time is not well characterized in human stroke, logarithmic and sigmoidal growth patterns have been shown in various experimental animal stroke models depending on sampling resolution and range of time interval. 35,36 Both recanalization groups showed initially faster infarct volume increase at shorter treatment intervals up to 18 hours followed by a tail of asymptotic growth tapering off beyond 22 hours. This was above a reported estimated range for the average duration of nonlacunar lesion evolution for supratentorial strokes (10 hours, range 6 to 18 hours) 34 but corresponded to the range of dynamic time curves of penumbra in human and animal studies.…”
Section: Discussionmentioning
confidence: 98%
“…Dynamic progression of lesion volume over time is not well characterized in human stroke, logarithmic and sigmoidal growth patterns have been shown in various experimental animal stroke models depending on sampling resolution and range of time interval. 35,36 Both recanalization groups showed initially faster infarct volume increase at shorter treatment intervals up to 18 hours followed by a tail of asymptotic growth tapering off beyond 22 hours. This was above a reported estimated range for the average duration of nonlacunar lesion evolution for supratentorial strokes (10 hours, range 6 to 18 hours) 34 but corresponded to the range of dynamic time curves of penumbra in human and animal studies.…”
Section: Discussionmentioning
confidence: 98%
“…The morphology of the growth function is not well-defined for human stroke and is model-specific in various experimental animal stroke models, 4 with a logarithmic pattern being most common 5,6 but sigmoidal 7 and other patterns also observed. Growth patterns in the geometrically more complex human cerebrum may differ from those in the rodent.…”
Section: The Growth Function Of An Ischemic Strokementioning
confidence: 99%
“…Nevertheless, both studies agree that nitroimidazoles will show substantial retention in the moderately to severely hypoperfused tissue, provided it is still viable. Recently, Saita et al 30 reported on 18 F-FMISO ex vivo autoradiography in rats subjected to 2-hour MCAO. Rats were injected at varying time points from occlusion (0.5 to 22 hour) and euthanized 2 hour later, and tracer retention was compared to triphenyltetrazolium chloride (TTC) postmortem staining.…”
Section: Takasawa Et Al Hypoxia Imaging In Ischemic Strokementioning
confidence: 99%